Flame-retardant modified wear-resistant polyester fiber and preparation method thereof

By combining nitrogen-modified carbon dot dispersants and modified fillers with modified polyethylene terephthalate, a multi-level flame retardant system is formed, which solves the problem of insufficient flame retardancy and abrasion resistance of polyester fibers, and achieves an improvement in efficient flame retardancy and abrasion resistance.

CN120967539AActive Publication Date: 2025-11-18SUZHOU YIMENG NEW MATERIAL TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202511249496.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-03
Publication Date
2025-11-18
Estimated Expiration
2045-09-03

AI Technical Summary

Technical Problem

The flame retardancy and abrasion resistance of existing polyester fibers need to be further improved. Traditional flame retardants and abrasion modification technologies have problems such as poor compatibility, low flame retardancy efficiency, and decreased material performance.

Method used

A nitrogen-modified carbon dispersant and modified filler are combined with modified polyethylene terephthalate to form a phosphorus-containing heterocyclic structure through a high-temperature and high-pressure reaction, which promotes the formation of a dense carbon layer. A multi-level flame retardant system of glass flakes and nano-silica is used to enhance the interfacial bonding and physical barrier.

Benefits of technology

It significantly improves the flame retardant efficiency and abrasion resistance of polyester fibers, and the incorporation of flame retardants in the form of chemical bonds enhances the thermal stability and mechanical strength of the material, while reducing dripping and friction damage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a flame-retardant modified wear-resistant polyester fiber and a preparation method thereof, belongs to the technical field of polyester fibers, and aims to solve the technical problem that the flame retardance and wear resistance of polyester fibers need to be further improved in the prior art. The preparation method specifically comprises the following steps: reacting DDP, a nitrogen modified carbon dot dispersant, terephthalic acid, ethylene glycol and an additive to obtain modified polyethylene glycol terephthalate, and carrying out melt extrusion and spinning on the modified polyethylene glycol terephthalate, ethylene glycol and a modified filler to obtain the wear-resistant polyester fiber. According to the invention, the polyethylene glycol terephthalate is modified, the modified filler is added, the effects of inhibiting combustion and preventing spreading are formed through the molecular-level chemical flame retardance of the modified polyethylene glycol terephthalate and the physical barrier of the filler, and the wear resistance of the material is improved through the combined action of the flaky and granular structures of the filler.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of polyester fibers, in particular to a flame-retardant modified wear-resistant polyester fiber and a preparation method thereof. BACKGROUND

[0002] Polyethylene terephthalate (PET) polyester fibers have become the core raw material in the fields of textile industry, filtration material, packaging material, etc. due to their high strength, good wrinkle resistance, and chemical corrosion resistance, etc. and play an important role in the national economy. However, the limiting oxygen index of polyester fibers is low, only 20%~22%, which belongs to flammable fibers. At the same time, a large amount of flammable substances are easily produced during the thermal decomposition of polyester fibers, which can easily cause fire and secondary combustion caused by molten droplets after burning, thus limiting their wide application.

[0003] The traditional additive flame retardant of the preparation process of polyester fibers mainly includes inorganic flame retardant. The inorganic flame retardant is an inorganic substance, which has poor compatibility with high polymer materials due to large polarity difference. The inorganic flame retardant is prone to agglomeration and causes the decrease of the mechanical properties of fibers. Although the halogen-based flame retardant has significant flame-retardant effect, it releases corrosive gas during combustion, which does not meet the environmental protection requirements.

[0004] The traditional phosphorus-based flame retardant is prone to volatilization or decomposition during the melt processing of polyester, which leads to the decrease of the flame-retardant efficiency and even the production of corrosive gas. The wear resistance of polyester fibers is better than that of natural fibers, but the strength of polyester fibers is still prone to attenuation in high-frequency friction scenarios due to surface wear. The conventional wear resistance modification technology mainly introduces small defects in the silica filler filling material. However, the conventional single nano-silica has low chemical affinity with the polyester matrix. During the friction process, the agglomerates formed by the silica and the polyethylene terephthalate molecular chain are not deformed in coordination due to stress, which becomes a stress concentration area, thus the wear resistance cannot be well played. SUMMARY

[0005] The present application relates to the technical field of polyester fibers, in particular to a flame-retardant modified wear-resistant polyester fiber and a preparation method thereof.

[0006] The technical problems to be solved by the present application are to provide a flame-retardant modified wear-resistant polyester fiber and a preparation method thereof, which can further improve the flame retardance and wear resistance of the polyester fiber.

[0007] S1, DDP, nitrogen modified carbon dot dispersant, terephthalic acid and antimony trioxide are added to the reaction kettle under nitrogen protection and stirred, the temperature is raised to 260-280℃, the pressure is raised to 320-340kPa to discharge the water in the system, when the reaction is to no excess water discharge, reduce to normal pressure, add triphenyl phosphite, hydrolysis resistant agent and ethylene glycol, react for 30-50min, get modified polyethylene terephthalate precursor;

[0008] S2, the temperature of the reaction system is raised to 270-290℃, vacuum to negative pressure 0.1MPa, reaction 1h, fill nitrogen into the reaction kettle to make the melt in the kettle extruded into cold water to quench, get modified polyethylene terephthalate.

[0009] S3, the modified polyethylene terephthalate, ethylene glycol and modified filler are added to the twin screw extruder and blended and extruded, then melt spinning on the spinning machine, after winding and drawing, get wear-resistant polyester fiber.

[0010] The synthesis mechanism of modified polyethylene terephthalate is:

[0011]

[0012] In the formula, R: The asterisk indicates the connection site of R.

[0013] After the nitrogen modified carbon dot dispersant is added to the reaction kettle, the hydroxyl and carboxyl groups on the surface can be combined with the carboxyl groups of terephthalic acid and the hydroxyl functional groups of ethylene glycol through hydrogen bonding to form a stable EG / gCDs / DDP dispersion system; terephthalic acid and ethylene glycol undergo reversible esterification reaction to generate bis-hydroxyethyl terephthalate at high temperature and high pressure; high vacuum is extracted in the final polycondensation stage to reduce the ethylene glycol partial pressure, which promotes the balance to move to high molecular weight polyethylene terephthalate, and the phosphorus-containing heterocyclic oligomer intermediate of DDP undergoes ester exchange and polycondensation reaction with bis-hydroxyethyl terephthalate to insert the phosphorus-containing heterocyclic structure into the polyethylene terephthalate backbone.

[0014] Further, in step S1, the mass ratio of DDP, nitrogen modified carbon dot dispersant, terephthalic acid, antimony trioxide, triphenyl phosphite, hydrolysis resistant agent and ethylene glycol is 8:1:700:0.7:1.4:2.1:314; the hydrolysis resistant agent is hydrolysis resistant agent 5500; in step S3, the mass ratio of modified polyethylene terephthalate, ethylene glycol and modified filler is 80-90:5-15:1-3; the temperature of the twin screw extruder from the feeding section to the head is 240℃, 260℃, 270℃, 280℃, 265℃ in turn; the screw rotation speed is 70-90r / min; the spinning temperature of the spinning machine is 265-280℃, and the spinning speed is 800-1000m / min.

[0015] In step S1, the preparation method of the nitrogen-modified carbon dot dispersant is as follows:

[0016] A1, gelatin and deionized water are added to a beaker, the temperature is raised to 60-80℃, tetrazole is added, and stirring is performed for 30-60min to obtain a mixed solution;

[0017] A2, the mixed solution is transferred to a high-pressure reaction kettle, the temperature is raised to 160-200℃, and reaction is performed for 8-12h, followed by post-treatment to obtain the nitrogen-modified carbon dot dispersant.

[0018] Preparation mechanism of the nitrogen-modified carbon dot dispersant:

[0019] High temperature causes the peptide bond and carbon chain of the gelatin to break, generating small molecular fragments, the small molecular fragments are condensed through dehydration, decarboxylation and other reactions, and then undergo cyclization, and the cyclization products are further polymerized to form a conjugated aromatic skeleton composed of sp 2 hybrid carbon, and finally form a nanometer carbon core; tetrazole undergoes heterocyclic rupture under high temperature and high pressure to release nitrogen-containing active intermediates, which combine with the unsaturated carbon sites of the carbon core to further introduce nitrogen atoms, and the surface of the carbon dots retains some polar groups that are not completely carbonized, which form hydrogen bonds with water molecules, allowing the carbon dots to be stably dispersed in water to obtain the nitrogen-modified carbon dot dispersant.

[0020] Further, in step A1, the amount ratio of the gelatin, deionized water and tetrazole is 1g:1g:20mL; in step A2, the post-treatment step includes: after the reaction is completed, the reaction liquid is transferred to a round-bottom flask of a rotary evaporator, the temperature is 40-50℃, negative pressure is extracted to 0.1MPa, and low-boiling substances are evaporated to obtain the nitrogen-modified carbon dot dispersant.

[0021] Further, the preparation method of the modified filler is as follows: the pretreated glass flake and silica dispersion liquid are added to a three-necked flask, ultrasonic dispersion is performed for 20-30min, KH-560 solution is added dropwise to the system, the temperature is raised to 60-70℃, reaction is performed for 3-4h, and post-treatment is performed to obtain the modified filler.

[0022] Preparation mechanism of the modified filler:

[0023] The silane coupling agent is hydrolyzed into a silanol group in the solution, and a large number of hydroxyl groups exist on the surfaces of the glass flake and the silica, which undergo dehydration condensation reaction with the silanol group to form stable covalent bonds, so that the silane coupling agent molecules are anchored on the surfaces of the two fillers to form a unified epoxy group active layer, and the modified filler is obtained.

[0024] Further, the treatment method of the pretreated glass flake is as follows: the glass flake and 5wt% hydrochloric acid solution are added into a beaker at a solid-liquid ratio of 1:10, the temperature is increased to 60-80 DEG C, stirring for 2-3h, then washed with deionized water until neutral, dried in a 60-80 DEG C vacuum drying oven until constant weight, to obtain the pretreated glass flake.

[0025] The synthesis mechanism of the pretreated glass flake is as follows:

[0026] The acidic environment of hydrochloric acid can promote the partial hydrolysis of the surface silicon dioxide of the glass flake, and the silicon-oxygen bond in the silicate framework is broken under acidic conditions to generate more active hydroxyl groups.

[0027] Further, the dosage ratio of the pretreated glass flake, the silicon dioxide dispersion liquid and the KH-560 solution is 2.5g:20mL:2.5mL; the KH-560 solution is composed of gamma-glycidyl ether propyltrimethoxysilane and anhydrous ethanol at a dosage ratio of 1g:45mL:5mL; the silicon dioxide dispersion liquid is composed of nanosilica and anhydrous ethanol at a dosage ratio of 1g:20mL; the post-treatment method comprises: after the reaction is completed, the reaction liquid is cooled to room temperature, centrifuged, the precipitate is washed with anhydrous ethanol for 2-3 times by ultrasonic, the filter cake is dried in a 60-80 DEG C vacuum drying oven until constant weight, and is ground through a 300 mesh sieve to obtain the modified filler.

[0028] The application further provides a flame-retardant modified wear-resistant polyester fiber prepared by the above flame-retardant modified wear-resistant polyester fiber preparation method

[0029] The application has the following beneficial effects:

[0030] 1. In the combustion process, the phosphorus element in DDP catalyzes the dehydration and cyclization reaction of the polyethylene terephthalate molecular chain, promotes the formation of a dense carbon layer, the carbon layer insulates heat and oxygen, prevents the further combustion of the matrix, and reduces the molten dripping at high temperature; the carboxyl groups of the succinic acid segment combine with the unreacted hydroxyl groups in the polyethylene terephthalate polycondensation reaction, so that the DDP is connected to the polyethylene terephthalate molecular chain in the form of a chemical bond, avoiding the migration and loss of the flame retardant in processing or use, and improving the flame-retardant durability; meanwhile, the phosphorus element of DDP and the nitrogen element on the surface of the carbon dot form a phosphorus-nitrogen synergistic effect, the nitrogen element can promote the formation of a more stable carbon layer of the oxidation product of phosphorus, and the inert gas such as ammonia gas produced by the decomposition of nitrogen further dilutes the combustible gas, greatly improving the flame-retardant efficiency.

[0031] 2、The modified filler of the present application is formed by glass flake and silicon dioxide to form a multi-stage flame retardant system, the glass flake is a flaky structure with a high aspect ratio, which can be oriented in the axial or radial direction in the fiber to form a multi-layer physical barrier to block the diffusion of oxygen and flammable gas, inhibit the direct contact of flame with the matrix, and the nano-silicon dioxide is a nano-sized particle which is dispersed in the matrix and can act as a carbon nucleus at high temperature to promote the modified polyethylene terephthalate to form a more fine carbon layer, reduce the carbon layer porosity, and improve the mechanical strength and wear resistance of the carbon layer, the flaky structure of the glass flake can slightly slide to convert sliding friction into rolling friction, reduce the friction coefficient, and the particle shape of the silicon dioxide improves the strength of the matrix and enhances the wear resistance, and the two together improve the wear resistance of the material.

[0032] 3、The glass flake and nano-silicon dioxide in the present application are modified by silane coupling agent, and epoxy groups are introduced on the surface, which can form chemical bonds or strong interactions with the polyethylene terephthalate molecular chain, improve the interfacial bonding force between the filler and the matrix, and play a physical support role at high temperature to delay the thermal shrinkage and decomposition of the matrix, and the inorganic filler itself is resistant to high temperature, thus improving the thermal stability of the material as a whole; the succinic acid segment and the methylene linking group have good segment rotation freedom, when DDP is introduced into the polyethylene terephthalate molecular chain, the flexible segment can break the dense packing of the original rigid aromatic ring of polyethylene terephthalate, so that the interaction force between the molecular chains is moderately weakened, and the segment is more prone to rotation and stretching when stretched, providing space for the improvement of elongation at break, at the same time, the carboxyl group and the amino and hydroxyl groups of the nitrogen-modified gelatin carbon dots can form hydrogen bonds, further strengthening the interfacial bonding between the carbon dots and the polyethylene terephthalate matrix, so that the nano-dispersed phase more effectively participates in stress dispersion, reducing local fracture when stretched. DETAILED DESCRIPTION

[0033] The technical solutions of the present application will be described below in conjunction with the embodiments, obviously, the described embodiments are only a part of the embodiments of the present application, not all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor belong to the scope of protection of the present application.

[0034] In the present application, the gelatin is from Guangzhou Yuanda New Material Co., Ltd., with CAS number 9000-70-8;

[0035] In the present application, KH-560 is gamma-glycidoxypropyltrimethoxysilane, from Shanghai Yihai Biological Technology Co., Ltd., with CAS number 2530-83-8;

[0036] In the present application, the glass flake is from Dachengxian Hengze Anti-corrosion Material Factory, with item number 06;

[0037] In the present application, DDP is [(6-oxo-6H-dibenzo[c,e][l,2]oxaphosphorin-6-yl)methyl] butanedioic acid, from Hubei Jianchu Biomedicals Co., Ltd., CAS No. 63562-33-4, with a purity of 99%.

[0038] Example 1

[0039] The present embodiment provides a flame-retardant modified wear-resistant polyester fiber and a preparation method thereof, comprising the following steps:

[0040] S1, preparing nitrogen-modified carbon dot dispersant

[0041] Weighing: 10 g of gelatin and 20 mL of deionized water are added to a beaker, the temperature is raised to 60°C, 10 g of tetrazole is added, and stirring is performed for 30 min to obtain a mixed solution;

[0042] Transfer 20 mL of the mixed solution to a high-pressure reaction kettle, raise the temperature to 160°C, and react for 8 h. After the reaction is completed, cool to room temperature, centrifuge, filter with a 0.22 μm needle filter membrane, and obtain the nitrogen-modified carbon dot dispersant.

[0043] S2, preparing modified filler

[0044] The silica dispersion solution is mixed by mixing 1 g of nanosilica and 20 mL of anhydrous ethanol; the KH-560 solution is mixed by mixing 1 g of γ-glycidyl ether propyltrimethoxysilane and 45 mL of anhydrous ethanol in a weight ratio of 1 g:45 mL:5 mL, and is ready for use;

[0045] Weighing: 10 g of glass flake and 100 mL of 5wt% hydrochloric acid solution are added to a beaker, the temperature is raised to 60°C, stirring is performed for 2 h, then washed with deionized water until neutral, and dried in a 60°C vacuum drying oven to constant weight to obtain pretreated glass flake;

[0046] Weighing: 25 g of pretreated glass flake and 200 mL of silica dispersion solution are added to a three-necked flask, ultrasonic dispersion is performed for 20 min, 25 mL of KH-560 solution is added dropwise to the system, the temperature is raised to 60°C, and reaction is performed for 3 h. After the reaction is completed, the reaction liquid is cooled to room temperature, centrifuged, the precipitate is ultrasonically washed with anhydrous ethanol for 2 times, the filter cake is placed in a 60°C vacuum drying oven to dry to constant weight, and is ground through a 300 mesh sieve to obtain the modified filler.

[0047] S3, preparing modified polyethylene terephthalate

[0048] Weighing: 8 g of DDP, 1 g of nitrogen-modified carbon dot dispersant, 700 g of terephthalic acid, and 0.7 g of antimony trioxide are added to a reaction kettle under nitrogen protection and stirred, the temperature is raised to 260℃, the pressure is raised to 320kPa to remove water from the system, when the reaction is completed without excess water, reduce to normal pressure, add 1.4 g of triphenyl phosphite, 2.1 g of hydrolysis inhibitor, and 314 g of ethylene glycol, and react for 30 min to obtain a modified polyethylene terephthalate precursor;

[0049] The temperature of the reaction system is raised to 270℃, vacuum is applied to a negative pressure of 0.1 MPa, and the reaction is carried out for 1 h. Nitrogen is filled into the reaction kettle to extrude the melt in the kettle into cold water for quenching, and a modified polyethylene terephthalate is obtained.

[0050] S4, wear-resistant polyester fiber

[0051] 80 g of modified polyethylene terephthalate, 5 g of ethylene glycol, and 1 g of modified filler are added to a twin-screw extruder for blending and extrusion. The temperature of each section of the twin-screw extruder from the feeding section to the die head is 240℃, 260℃, 270℃, 280℃, and 265℃, respectively, and the screw rotation speed is 70 r / min. Then, melt spinning is carried out on a spinning machine with a spinning temperature of 265℃ and a spinning speed of 800 m / min. After winding and drawing, a wear-resistant polyester fiber is obtained.

[0052] Example 2

[0053] The present embodiment provides a flame-retardant modified wear-resistant polyester fiber and a preparation method thereof, comprising the following steps:

[0054] S1, preparation of nitrogen-modified carbon dot dispersant

[0055] Weighing: 10 g of gelatin and 20 mL of deionized water are added to a beaker, the temperature is raised to 70℃, 10 g of tetrazole is added, and stirring is carried out for 45 min to obtain a mixed solution;

[0056] 20 mL of the mixed solution is transferred to a high-pressure reaction kettle, the temperature is raised to 180℃, and the reaction is carried out for 10 h. After the reaction is completed, the reaction kettle is cooled to room temperature, centrifuged, filtered with a 0.22 μm needle filter membrane, and a nitrogen-modified carbon dot dispersant is obtained.

[0057] S2, preparation of modified filler

[0058] The silica dispersion solution is mixed by nano-silica and anhydrous ethanol at a ratio of 1 g:20 mL. The KH-560 solution is mixed by γ-glycidyl ether propyltrimethoxysilane and anhydrous ethanol at a ratio of 1 g:45 mL:5 mL, and is ready for use;

[0059] Weighing: 10 g of glass flake and 100 mL of 5 wt% hydrochloric acid solution are added to a beaker, the temperature is raised to 70℃, stirring for 2.5 h, then washed with deionized water to neutral, dried in a 70℃ vacuum drying oven to constant weight, to obtain pretreated glass flake;

[0060] Weighing: 25 g of pretreated glass flake and 200 mL of silica dispersion liquid are added to a three-necked flask, ultrasonic dispersion for 25 min, 25 mL of KH-560 solution is added dropwise to the system, the temperature is raised to 65℃, and the reaction is carried out for 3.5 h. After the reaction is completed, the reaction liquid is cooled to room temperature, centrifuged, the precipitate is washed with anhydrous ethanol for 2 times by ultrasonic, the filter cake is placed in a 70℃ vacuum drying oven to dry to constant weight, and ground through a 300 mesh sieve to obtain a modified filler.

[0061] S3, preparation of modified polyethylene terephthalate

[0062] Weighing: 8 g of DDP, 1 g of nitrogen-modified carbon dot dispersant, 700 g of terephthalic acid and 0.7 g of antimony trioxide are added to a reaction kettle under nitrogen protection and stirred, the temperature is raised to 270℃, the pressure is raised to 330 kPa to remove water from the system, when the reaction is completed without excess water, the pressure is reduced to normal pressure, 1.4 g of triphenyl phosphite, 2.1 g of hydrolysis inhibitor and 314 g of ethylene glycol are added, and the reaction is carried out for 40 min to obtain a modified polyethylene terephthalate precursor;

[0063] The temperature of the reaction system is raised to 280℃, vacuum is applied to a negative pressure of 0.1 MPa, and the reaction is carried out for 1 h. Nitrogen is filled into the reaction kettle to extrude the melt in the kettle into cold water for quenching to obtain modified polyethylene terephthalate.

[0064] S4, wear-resistant polyester fiber

[0065] 85 g of modified polyethylene terephthalate, 10 g of ethylene glycol and 2 g of modified filler are added to a twin-screw extruder for blending and extrusion. The temperature of each section of the twin-screw extruder from the feeding section to the die head is 240℃, 260℃, 270℃, 280℃ and 265℃, respectively, and the screw rotation speed is 80 r / min. Then, melt spinning is carried out on a spinning machine, the spinning temperature of the spinning machine is 270℃, and the spinning speed is 900 m / min. After winding and drawing, a wear-resistant polyester fiber is obtained.

[0066] Example 3

[0067] The present embodiment provides a flame-retardant modified wear-resistant polyester fiber and a preparation method thereof, which comprises the following steps:

[0068] S1, preparation of nitrogen-modified carbon dot dispersant

[0069] Weighing: 10 g of gelatin and 20 mL of deionized water are added to a beaker, the temperature is raised to 80℃, 10 g of tetrazole is added, stirring for 60 min to obtain a mixed solution;

[0070] Transfer 20 mL of the mixed solution to a high-pressure reaction kettle, raise the temperature to 200℃, react for 12 h, after the reaction is completed, cool to room temperature, centrifuge, filter with a 0.22 μm needle filter membrane, and nitrogen-modified carbon dot dispersant is obtained.

[0071] S2, preparation of modified filler

[0072] The silica dispersion solution is mixed by nano-silica and anhydrous ethanol at a ratio of 1 g:20 mL; the KH-560 solution is mixed by γ-glycidoxypropyltrimethoxysilane and anhydrous ethanol at a ratio of 1 g:45 mL:5 mL, and is ready for use;

[0073] Weighing: 10 g of glass flake and 100 mL of 5wt% hydrochloric acid solution are added to a beaker, the temperature is raised to 80℃, stirring for 3 h, then washed with deionized water until neutral, and dried in a 80℃ vacuum drying oven to constant weight to obtain pretreated glass flake;

[0074] Weighing: 25 g of pretreated glass flake and 200 mL of silica dispersion solution are added to a three-necked flask, ultrasonic dispersion for 30 min, 25 mL of KH-560 solution is added dropwise to the system, the temperature is raised to 70℃, and the reaction is carried out for 4 h, after the reaction is completed, the reaction liquid is cooled to room temperature, centrifuged, the precipitate is ultrasonically washed with anhydrous ethanol for 3 times, the filter cake is placed in a 80℃ vacuum drying oven to dry to constant weight, and is ground through a 300 mesh sieve to obtain a modified filler.

[0075] S3, preparation of modified polyethylene terephthalate

[0076] Weighing: 8 g of DDP, 1 g of nitrogen-modified carbon dot dispersant, 700 g of terephthalic acid and 0.7 g of antimony trioxide are added to a reaction kettle under nitrogen protection, stirring, the temperature is raised to 280℃, the pressure is raised to 340 kPa to remove water from the system, when the reaction is completed without excess water, the pressure is reduced to normal pressure, 1.4 g of triphenyl phosphite, 2.1 g of water resistance agent and 314 g of ethylene glycol are added, and the reaction is carried out for 50 min to obtain a modified polyethylene terephthalate precursor;

[0077] The temperature of the reaction system is raised to 290℃, vacuum is applied to a negative pressure of 0.1 MPa, and the reaction is carried out for 1 h, nitrogen is filled into the reaction kettle to extrude the melt in the kettle into cold water to quench, and a modified polyethylene terephthalate is obtained.

[0078] S4, wear-resistant polyester fiber

[0079] Put 90 g of modified polyethylene terephthalate, 15 g of ethylene glycol and 3 g of modified filler into a twin-screw extruder for blending and extrusion. The temperature of each section of the twin-screw extruder from the feeding section to the head is 240℃, 260℃, 270℃, 280℃ and 265℃ in turn, and the screw rotation speed is 90 r / min. Then melt spinning is carried out on a spinning machine, the spinning temperature of the spinning machine is 280℃, the spinning speed is 1000 m / min, and after winding and drawing, wear-resistant polyester fibers are obtained.

[0080] Comparative Example 1

[0081] The difference between this comparative example and Example 3 is that no tetrazole is added in step S1.

[0082] Comparative Example 2

[0083] The difference between this comparative example and Example 3 is that step S2 is cancelled and silica is used instead of modified filler.

[0084] Comparative Example 3

[0085] The difference between this comparative example and Example 3 is that no DDP is added in step S3.

[0086] Comparative Example 4

[0087] The difference between this comparative example and Example 3 is that no nitrogen-modified carbon dot dispersant is added in step S3.

[0088] Performance test:

[0089] The flame retardant properties of the polyester fibers prepared in Examples 1-3 and Comparative Examples 1-4 are determined according to the standard FZ / T 50029-2015 “Synthetic fiber raw material chip flame retardant property test method oxygen index method”;

[0090] The elongation at break of the polyester fibers prepared in Examples 1-3 and Comparative Examples 1-4 is determined according to the standard GB / T 14344-2022 “Chemical fiber filament tensile property test method”.

[0091] The wear resistance of the polyester fibers prepared in Examples 1-3 and Comparative Examples 1-4 is determined according to the standard GB / T 19089-2012 “Rubber or plastic coated fabric wear resistance determination Martin Dale method”.

[0092] The mass loss rate of the thermal stability of the polyester fibers prepared in Examples 1-3 and Comparative Examples 1-4 is determined according to the standard GB / T 33047.1-2016 “Plastics Polymers Thermogravimetric Method (TG) Part 1: General”, and the specific test results are shown in Table 1.

[0093] Table 1-Performance detection data table of the sample

[0094] Group item Oxygen index / OI Elongation at break / % Mass loss rate / % Wear resistance / damage level Example 1 27 35 25 0 Example 2 28 36 23 0 Example 3 28 35 24 0 Comparative Example 1 23 23 33 2 Comparative Example 2 24 26 32 3 Comparative Example 3 21 25 31 2 Comparative Example 4 22 22 30 2

[0095] Data analysis:

[0096] Comparative analysis of the data in the above table, the polyester fiber prepared by the present application, the oxygen index reaches 28, the elongation at break reaches 36%, the mass loss rate reaches 23%, the wear resistance is measured without damage, the examples are better than the comparative examples, which shows that the polyethylene terephthalate is modified, the modified filler is added, the molecular level chemical flame retardant of the modified polyethylene terephthalate and the physical barrier of the filler are combined, the effect of inhibiting combustion and preventing spread is formed, and the flaky and granular structure of the filler acts together to improve the wear resistance of the material.

[0097] Comparative example 1 and example, the phosphorus element of DDP and the nitrogen element on the surface of carbon dots form a phosphorus-nitrogen synergistic effect, the nitrogen element can promote the formation of a more stable carbon layer of the oxidation product of phosphorus, and the inert gas such as ammonia gas produced by the decomposition of nitrogen further dilutes the combustible gas, greatly improving the flame retardant efficiency.

[0098] Comparative example 2 and example, the glass flake is a flaky structure with high aspect ratio, which can be arranged in the axial or radial direction in the fiber, forming a multilayer physical barrier to block the diffusion of oxygen and combustible gas, and inhibiting the direct contact of flame with the matrix, and the granular silica acts together to improve the wear resistance of the material.

[0099] Comparative example 3 and example, the phosphorus element in DDP catalyzes the dehydration and cyclization reaction of polyethylene terephthalate molecular chain, promotes the formation of a dense carbon layer, the carbon layer blocks heat and oxygen, prevents the further combustion of the matrix, and improves the flame retardant performance of the material.

[0100] Comparative example 4 and example, the phosphorus element of DDP and the nitrogen element on the surface of carbon dots form a phosphorus-nitrogen synergistic effect, the nitrogen element can promote the formation of a more stable carbon layer of the oxidation product of phosphorus, and the inert gas such as ammonia gas produced by the decomposition of nitrogen further dilutes the combustible gas, greatly improving the flame retardant efficiency.

[0101] The preferred embodiments of the present application disclosed above are only used to help explain the present application. The preferred embodiments do not describe all the details, nor limit the present application to the specific embodiments. Obviously, many modifications and changes can be made according to the content of the present application. The present application selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present application, so that those skilled in the art can well understand and utilize the present application. The present application is limited by the claims and their entire scope and equivalents.

Claims

1. A method for preparing flame-retardant modified abrasion-resistant polyester fiber, characterized in that, Includes the following steps: S1. Add DDP, nitrogen-modified carbon dot dispersant, terephthalic acid and antimony trioxide to a nitrogen-protected reactor and stir. Raise the temperature to 260-280℃ and the pressure to 320-340kPa to remove water from the system. When no excess water is removed, reduce the pressure to atmospheric pressure and add triphenyl phosphite, anti-hydrolysis agent and ethylene glycol. React for 30-50 minutes to obtain the modified polyethylene terephthalate precursor. S2. Raise the temperature of the reaction system to 270-290℃, evacuate to a negative pressure of 0.1MPa, react for 1 hour, and then fill the reaction vessel with nitrogen gas until the melt inside the vessel is squeezed into cold water for quenching to obtain modified polyethylene terephthalate. S3. Modified polyethylene terephthalate, ethylene glycol and modified filler are added to a twin-screw extruder for co-extrusion, and then melt-spun on a spinning machine. After winding and stretching, wear-resistant polyester fiber is obtained.

2. The method for preparing flame-retardant modified abrasion-resistant polyester fiber according to claim 1, characterized in that, In step S1, the mass ratio of DDP, nitrogen-modified carbon dispersant, terephthalic acid, antimony trioxide, triphenyl phosphite, antihydrolysis agent, and ethylene glycol is 8:1:700:0.7:1.4:2.1:314; the antihydrolysis agent is antihydrolysis agent 5500. In step S3, the mass ratio of modified polyethylene terephthalate, ethylene glycol, and modified filler is 80-90:5-15:1-3; the temperatures of the twin-screw extruder from the feed section to the die head are 240℃, 260℃, 270℃, 280℃, and 265℃ respectively; the screw speed is 70-90 r / min; the spinning temperature of the spinning machine is 265-280℃, and the spinning speed is 800-1000 m / min.

3. The method for preparing flame-retardant modified abrasion-resistant polyester fiber according to claim 1, characterized in that, In step S1, the preparation method of the nitrogen-modified carbon dot dispersant is as follows: A1. Add gelatin and deionized water to a beaker, raise the temperature to 60-80℃, add tetrazolium, stir for 30-60 minutes to obtain a mixed solution; A2. Transfer the mixed solution to a high-pressure reactor, raise the temperature to 160-200℃, react for 8-12 hours, and then perform post-treatment to obtain nitrogen-modified carbon dot dispersant.

4. The method for preparing flame-retardant modified abrasion-resistant polyester fiber according to claim 3, characterized in that, In step A1, the ratio of gelatin, tetrazolium, and deionized water is 1g:1g:20mL; in step A2, the post-processing steps include: after the reaction is completed, the reaction solution is transferred to a round-bottom flask of a rotary evaporator, the temperature is 40-50℃, the negative pressure is drawn to 0.1MPa, and low-boiling substances are evaporated to obtain nitrogen-modified carbon dot dispersant.

5. The method for preparing flame-retardant modified abrasion-resistant polyester fiber according to claim 1, characterized in that, The modified filler is prepared by adding pretreated glass flakes and silica dispersion into a three-necked flask, ultrasonically dispersing for 20-30 min, adding KH-560 solution dropwise to the system, heating to 60-70℃, reacting for 3-4 h, and then post-processing to obtain the modified filler.

6. The method for preparing flame-retardant modified abrasion-resistant polyester fiber according to claim 5, characterized in that, The pretreated glass flakes are processed as follows: glass flakes and 5wt% hydrochloric acid solution are added to a beaker at a solid-liquid ratio of 1:10, the temperature is raised to 60-80℃, and the mixture is stirred for 2-3 hours. Then, the mixture is washed with deionized water until neutral and dried in a vacuum drying oven at 60-80℃ until constant weight to obtain pretreated glass flakes.

7. The method for preparing flame-retardant modified abrasion-resistant polyester fiber according to claim 5, characterized in that, The ratio of the pretreated glass flakes, silica dispersion, and KH-560 solution is 2.5g:20mL:2.5mL; the KH-560 solution is composed of γ-glycidyl etheroxypropyltrimethoxysilane, anhydrous ethanol, and deionized water in a ratio of 1g:45mL:5mL; the silica dispersion is composed of nano-silica and anhydrous ethanol in a ratio of 1g:20mL; the post-treatment method includes: after the reaction is completed, the reaction solution is cooled to room temperature, centrifuged, the precipitate is ultrasonically washed 2-3 times with anhydrous ethanol, the filter cake is dried in a vacuum drying oven at 60-80℃ to constant weight, and ground through a 300-mesh sieve to obtain the modified filler.

8. A flame-retardant modified abrasion-resistant polyester fiber, characterized in that, The flame-retardant modified abrasion-resistant polyester fiber is prepared by the method for preparing flame-retardant modified abrasion-resistant polyester fiber as described in any one of claims 1-7.

Citation Information

Patent Citations

  • Preparation of high glaze glass-based pearlescent pigment

    CN101434759A

  • Method for molding halogen-free flame-retardant thermoplastic polyester composition

    CN103660306A

  • Anticorrosion heat-resisting modified coating

    CN107345106A

  • Preparation method of glass-based pearlescent pigment with high glossiness

    CN116769329A

  • Method for preparing cationic dyeable flame-retardant high-strength polyester fiber

    US20250066955A1